Transnational Writing Program Administration - Martins, David S. (Book collections on Project MUSE., 2014)
"While local conditions remain at the forefront of writing program administration, transnational activities are slowly and thoroughly shifting the questions we ask about writing curricula, the space and place in which writing happens, and the cultural and linguistic issues at the heart of the relationships forged in literacy work. Transnational Writing Program Administration challenges taken-for-granted assumptions regarding program identity, curriculum and pedagogical effectiveness, logistics and quality assurance, faculty and student demographics, innovative partnerships and research, and the infrastructure needed to support writing instruction in higher education. Well-known scholars and new voices in the field extend the theoretical underpinnings of writing program administration to consider programs, activities, and institutions involving students and faculty from two or more countries working together and highlight the situated practices of such efforts. The collection brings translingual graduate students at the forefront of writing studies together with established administrators, teachers, and researchers and intends to enrich the efforts of WPAs by examining the practices and theories that impact our ability to conceive of writing program administration as transnational. This collection will enable writing program administrators to take the emerging locations of writing instruction seriously, to address the role of language difference in writing, and to engage critically with the key notions and approaches to writing program administration that reveal its transnationality"--